The lost book of Bonn : a novel [large type] - Labuskes, Brianna (Harper Large Print, an imprint of HarperCollinsPublishers, 2024)
"Germany, 1946: Emmy Clarke is a librarian not a soldier. But that doesn't stop the Library of Congress from sending her overseas to Germany to help the Monuments Men retrieve and catalog precious literature that was plundered by the Nazis. The Offenbach Archival Depot and its work may get less attention than returning art to its rightful owners, but for Emmy, who sees the personalized messages on the inside of the books and the notes in margins of pages, it feels just as important. On Emmy's first day at work, she finds a poetry collection by Rainer Maria Rilke, and on the title page is a handwritten dedication: "To Annelise, my brave Edelweiss Pirate." Emmy is instantly intrigued by the story behind the dedication and becomes determined to figure out what happened. The hunt for the rightful owner of the book leads Emmy to two sisters, a horrific betrayal, and an extraordinary protest against the Nazis that was held in Berlin at the height of the war. Nearly a decade earlier, hundreds of brave women gathered in the streets after their Jewish husbands were detained by the Gestapo. Through freezing rain and RAF bombings, the women faced down certain death and did what so few others dared to do under the Third Reich. They said no. Emmy grapples with her own ghosts as she begins to wonder if she's just chasing two more. What she finds instead is a powerful story of love, forgiveness, and courage that brings light to even the darkest of postwar days"--